PEMBERDAYAAN PENYANDANG DISABILITAS PADA PROGRAM PERMATABRAVE CORPORATE SOCIAL RESPONSIBILITY (CSR) BANK PERMATA TBK - Wahyudi, Ayuananda (Jurnal Ilmu Kesejahteraan Sosial HUMANITAS, 2023)
The right to access to work is one of the problems for persons with disabilities, many of them cannot find work due to their low educational background and lack of skills. Through empowerment such as the Corporate Social Responsibility (CSR) program that exists in every company, it can help persons with disabilities in meeting their daily needs by becoming worker or employee in a company. One company that has a CSR program for people with disabilities is Permata Bank. So based on this background, researchers are encouraged to conduct in-depth research on Corporate Social Responsibility (CSR), so that this thesis will be entitled: "Empowerment of Persons with Disabilities in PT Bank Permata Tbk's PermataBRAVE Corporate Social Responsibility (CSR) Program." This study aims to describe the results of implementing the empowerment of persons with disabilities in the PermataBRAVE CSR program at PT Bank Permata Tbk. The research method used is a qualitative descriptive approach with a purposive sampling informant selection technique. Data collection techniques in this study used in-depth interviews, observation and documentation. Based on the results of research that has been conducted regarding the empowerment of persons with disabilities in the PermataBRAVE CSR program at PT Bank Permata Tbk. , the PermataBRAVE program has activities for 1 month where later persons with disabilities have access to be able to work at PermataBank for 6 months with different divisions.